Analysis of the Molecular Mechanisms Governing the Stage-Specific Expression of a Prototypical Housekeeping Gene during Intraerythrocytic Development of P. falciparum - Wong, Eleanor H.; Hasenkamp, Sandra; Horrocks, Paul (Journal of molecular biology, 2011)
Gene expression during the intraerythrocytic development cycle of the human malarial parasite Plasmodium falciparum is subject to tight temporal control, resulting in a cascade of gene expression to meet the physiological demands of growth, replication, and reinvasion. The roles of the different molecular mechanisms that drive this temporal program of gene expression are poorly understood. Here we report the use of the bxb1 integrase system to reconstitute all aspects of the absolute and temporal control of the prototypical housekeeping gene encoding the proliferating cell nuclear antigen (Pfpcna) around an integrated luciferase reporter cassette. A quantitative analysis of the effect of the serial deletion of 5′ and 3′ genetic elements and sublethal doses of histone deacetylase inhibitors demonstrates that while the absolute control of gene expression could be perturbed, no effect on the temporal control of gene expression was observed. These data provide support for a novel model for the temporal control of potentially hundreds of genes during the intraerythrocytic development of this important human pathogen.